Google Maps-Based Puzzle Media for Spatial Intelligence Development on Social Studies Learning - Irena Novarlia (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
The focus of this research is an effort to develop spatial intelligence used google maps-based puzzle media on social studies learning in class VII A SMPN 1 Cimalaka. The method used is classroom action research. Determination of sample and study site is 38 students. Technical data using observation data, documentation and records. Data were analyzed by descriptive and statistical analysis features. The results showed that the individual activities of students had a significant increase with an average of 71.4% in cycle I, 78.4% in cycle II, and 84% in cycle III. Meanwhile, the group of learners experienced anaverage increase of 20% in the first cycle, 60% in cycle II, and 80% in cycle III. The results showed google maps-based puzzle media proved to be significantly can develop spatial intelligence as well as learning outcomes of students. Based on the research results, it is recommended that teachers can develop google maps-based puzzle media as an alternativesocial studies learning media, that the implementation will be successful if followed with sincerity ranging from planning, implementation and evaluation.